Xylanase - complex efficacy in high-energy diet for bulls finished in feedlot - Mikael Neumann; Guilherme Fernando Mattos Leão; Gabriela Letícia Dalai Vigne; Leslei Caroline dos Santos; Bruno José Venancio; André Dochwat (Acta Scientiarum. Animal Sciences, 2017)
Enzymes can be an interesting additive in high energy diets for feedlot cattle. However, literature is inconsistent on this subject. Thus, this study was conducted to evaluate animal performance of feedlot bulls receiving high energy diet, composed of a mixture of 85% whole corn grain and 15% protein-mineral-vitamin nucleus, without or with xylanase included in the diets. Diets consisted of: CON - diet without enzymes (Control) and ENZ - diet with enzymes (5 g animal day-1). Thirty-two bulls were used, with an average age of 11 ± 2 months, average initial weight of 365 ± 5 kg, and finished for 119 days in feedlot. The experimental design was completely randomized, consisting of two treatments and eight replications, where each replication was represented by a stall with two animals. ENZ increased the weight gain (1.69 vs. 1.33 kg day-1) and improved the feed conversion (4.60 vs. 6.03 kg-1) in the adaptation period of the animals. Animals receiving ENZ increased 1.65% of carcass yield and were 7.57% more efficient in the conversion of dry matter consumed into carcass gain in relation to CON. Carcass traits of feedlot-finished bulls were not altered by inclusion of enzymes. Xylanase-complex could increase efficiency in feedlot bulls.